Physical Neglect and Mental Violence Towards Children by Parents: An Analysis of Criminal Law - Dewi Magfirotul Akbar (Rechtenstudent, 2022)
Physical neglect and mental violence are types of violence against children whose provisions are regulated in several articles in the Criminal Code and Law No. 35 of 2014 concerning Child Protection. In the articles that regulate acts of physical neglect and mental violence, it is necessary to explain specifically regarding the types of acts of violence concerned so that efforts to protect victims can be carried out optimally. However, there are several articles in the Criminal Code and in the Child Protection Law that experience blurred norms due to limited explanations regarding the types of acts of violence. This study aims to find out how the systematic protection and views of positive law and Islamic criminal law regarding acts of physical neglect and mental violence against children committed by both biological parents. The method used is to use a type of normative juridical research through statutory and conceptual approaches. The conclusions of this study are: 1) Acts of physical neglect in the Criminal Code are regulated in articles 305, 306 and 307 and in Law No. 35 of 2014 are regulated in article 76B. The prohibition on acts of mental violence is regulated in Article 1 paragraph (15a). Meanwhile, according to Islamic criminal law, the act of violence is punishable by ta'zir because it is not regulated by the text. 2) Protection for victims of physical neglect has been regulated in article 71 of the Law on Child Protection and for victims of mental violence has been explained in article 69 of the Law on Child Protection. Meanwhile, according to Islamic criminal law, the nature of child protection is to fulfill all children's rights and provide treatment and protection from all things that can harm children, including life, property and so on.